2014
DOI: 10.1097/shk.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Ameliorate Sepsis-associated Acute Kidney Injury in Mice

Abstract: Treatment with MSCs can alleviate sepsis-associated AKI and improve survival in mice with polymicrobial sepsis. These effects may be mediated by the inhibition of IL-17 secretion and balance of the proinflammatory and anti-inflammatory states. Mesenchymal stem cells may be a potential new therapeutic agent for the prevention or reduction of sepsis-associated AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 34 publications
0
96
0
4
Order By: Relevance
“…40 Intravenous MSCs improve lung histology and decrease concentrations of proinfl ammatory cytokines in BAL fl uid after infection, 28,38 decrease concentrations of infl ammatory cytokines in cardiac tissue and improve cardiac function after intravenous LPS, 36 and also lower renal expression of proinfl ammatory cytokines and improve serological markers of kidney function after caecal ligation and puncture. 37 These eff ects occurred without substantial MSC localisation to the studied tissue, which suggests a paracrine mechanism. As with lung injury models, investigators have used infection models to identify paracrine factors that might contribute to the observed benefi ts of MSCs.…”
Section: Injury Model Msc Source Msc Delivery Methods Major Fi Nding Ementioning
confidence: 92%
See 1 more Smart Citation
“…40 Intravenous MSCs improve lung histology and decrease concentrations of proinfl ammatory cytokines in BAL fl uid after infection, 28,38 decrease concentrations of infl ammatory cytokines in cardiac tissue and improve cardiac function after intravenous LPS, 36 and also lower renal expression of proinfl ammatory cytokines and improve serological markers of kidney function after caecal ligation and puncture. 37 These eff ects occurred without substantial MSC localisation to the studied tissue, which suggests a paracrine mechanism. As with lung injury models, investigators have used infection models to identify paracrine factors that might contribute to the observed benefi ts of MSCs.…”
Section: Injury Model Msc Source Msc Delivery Methods Major Fi Nding Ementioning
confidence: 92%
“…37,38,[48][49][50][51] This antibacterial eff ect is partly mediated by improved phagocytic activity of host immune cells such as macrophages, 38,41 monocytes, 48 neutrophils, 49 and ITGAMpositive cells (monocytes, macrophages, and neutrophils). 38 Studies using ex-vivo human lungs have reported similar fi ndings.…”
Section: Antimicrobial Eff Ectsmentioning
confidence: 99%
“…The authors suggested that the inflammation largely contributed to the pathogenesis of AKI. [30] Similarly, Chancharoenthana and et al demonstrated that hypercytokinemia plays a more distinct role in sepsis-related AKI than in non-sepsis related AKI. [31] It has been determined that oxidative stress plays an important role in sepsis-related AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Como placebo se utilizó una inyección de fibroblastos, suero salino o MSC inactivados por shock térmico. El tratamiento de soporte consistió en antibióticos y volumen, los que fueron administrados a los grupos experimental y placebo [24][25][26][27][28][29] . El momento de la infusión y la dosis de MSCs fue variable entre los estudios.…”
Section: Sepsisunclassified